Factors Influencing the Purchasing Behavior of Traditional Chinese Medicine (TCM) in Malaysia - Li, Jia (2014)
As the improvement of age, more people witness the development of traditional culture. Traditional Chinese Medicine (TCM) is one of them and it becomes popular in the global because it does not have much side-effects on human bodies. However, the status of TCM in Malaysia is not very high, thus this study is to explore the factors that can influence the purchasing behavior of TCM in Malaysia. The research framework of this study uses Liao et al’ model (2008), and the whole study follows it. What’s more, SPSS 20 and PLS software are used to analysis the data that are collected from 300 respondents in 4 states of Malaysia. And lastly, there are 5 factors which include Suffering from Disease (SFD), Attitude towards TCM (ATT), TCM Knowledge (TK), People’s Influence (PI) and Usable Resources (UR) are found to have the significant influence on the Purchasing Behavior (PB) of TCM in Malaysia. According to the findings, the author gives some recommendations to the TCM sector in Malaysia in order to attract more people to use TCM products.